Direct analysis of ascorbic acid in food beverage samples by flow injection analysis using reduced graphene oxide sensor. (30th July 2020) - de Faria, Lucas Vinícius; Lisboa, Thalles Pedrosa; de Farias, Davi Marques; Araujo, Fausto Moreira; Machado, Mateus Moura; de Sousa, Rafael Arromba; Matos, Maria Auxiliadora Costa; Muñoz, Rodrigo Alejandro Abarza; Matos, Renato Camargo
Highlights: Simple and fast method for ascorbic acid determination in food beverage samples. The sample preparation method required only dilution in supporting electrolyte. Effect electrocatalytic of the rGO sensor for ascorbic acid oxidation. Important analytical tool for quality control in routine analyzes. The results obtained were statistically similar with Ultra-Fast Liquid Chromatography. Abstract: In this paper, a simple, sensitive and precise electroanalytical method was developed using flow injection analysis (FIA) with amperometric detection and reduced graphene oxide sensor for ascorbic acid determination in samples of multivitamin beverages, milk, fermented milk, and milk chocolate. The advantages of this sensor include a potential displacement of 450 mV and a 2-fold peak current increase for electrochemical oxidation of ascorbic acid, which resulted in a highly sensitive method. No interference of sample matrix was observed, avoiding solvent extraction procedures (samples were only diluted). The FIA allowed a high analytical frequency, approximately 96 injections per hour, together with adequate detection limit of 4.7 μmol L −1 . Good precision (RSD < 7%) and accuracy (recoveries between 91 and 108%) evidenced the robustness of the method. The method was compared with ultra-fast liquid chromatography (UFLC) obtaining statistically similar results (95% confidence level). The ascorbic acid content in samples varied from 0.065 to 2.53 mmol L −1 .